Three-dimensional virtual histology enabled through cytoplasm-specific X-ray stain for microscopic and nanoscopic computed tomography - Busse, Madleen; Mueller, Mark; Kimm, Melanie A.; Ferstl, Simone; Allner, Sebastian; Achterhold, Klaus; Herzen, Julia; Pfeiffer, Franz (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Many histological methods require staining of the cytoplasm, which provides instrumental details for diagnosis. One major limitation is the production of 2D images obtained by destructive preparation of 3D tissue samples. X-ray absorption micro- and nanocomputed tomography (microCT and nanoCT) allows for a nondestructive investigation of a 3D tissue sample, and thus aids to determine regions of interest for further histological examinations. However, application of microCT and nanoCT to biological samples (e.g., biopsies) is limited by the missing contrast within soft tissue, which is important to visualize morphological details. We describe an eosin-based preparation overcoming the challenges of contrast enhancement and selectivity for certain tissues. The eosin-based staining protocol is suitable for whole-organ staining, which then enables high-resolution microCT imaging of whole organs and nanoCT imaging of smaller tissue pieces retrieved from the original sample. Our results demonstrate suitability of the eosin-based staining method for diagnostic screening of 3D tissue samples without impeding further diagnostics through histological methods.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 3D imaging; 3D virtual histology; Cytoplasm-specific X-ray stain; MicroCT; NanoCT